Reading the Book of Job and Camus's La Peste during COVID-19 - Erwin Susanto (Indonesian Journal of Theology, 2020)
The pandemic crisis that is COVID-19 has caused unprecedented suffering throughout the world. At such a time, the religious person can legitimately ask why God allows this and how one’s faith might wrestle with such tragedy. In my search of the Scriptures to respond to these questions, I find the Book of Job to be a fruitful dialogue partner—be it in the way it urges one to consider aspects of suffering that are not apparent or in how it resists attempts at oversimplifying God’s character. In this essay, I compare the Book of Job with Albert Camus’s novel La Peste, the latter being set during an epidemic. I argue that both literary works provide space for a theological voice to recognize and articulate suffering in terms of divine justice; both works also enable one to resist any concrete framework for explaining suffering. I then suggest that La Peste complements one’s reading of Job as Scripture by highlighting both the importance of active response to suffering as well as the relational dimension of suffering in the world, which should prove to be helpful in this time of crisis and beyond.